Tightening robust price bounds for exotic derivatives. Issue 11 (2nd November 2019) - Lütkebohmert, Eva; Sester, Julian
Abstract : We investigate the optimal martingale transport problem under additional constraints and its application to robust price bounds for financial derivatives. More specifically, we derive improved price bounds by taking into account supplementary information about the variance of the returns on the underlying security. Such information can be extracted from market data and our theoretical and numerical results indeed show a significant tightening of price bounds. In this respect, our results have important implications for the practical applicability and relevance of robust price bounds.